2019
DOI: 10.15414/agrobiodiversity.2019.2585-8246.212-223
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Using Spices in Technology Soft-Ripened Goat Cheese

Abstract: The problem of balanced nutrition is one of the most important social problems in our time. In the context of changes in population nutrition and protein deficits, increasing attention is being paid to increasing the use of protein resources for nutritional purposes, including the creation of new products. The value of such products is determined not only by the amount of protein, but also by its quality. Goat's milk is rich in casein and albumin, which contain important amino acids for the human body. Soft-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…are used for their structure stabilization (Kochubei- Lytvynenko et al, 2018a;Ondrušíková et al, 2019;Kumbár et al, 2017). Free moisture is suitable environment for biochemical transformations, that is why during production and storage of butter pastes there is a danger of biochemical transformations of milk fat and other components, primarily proteins and carbohydrates limiting storage life of such products (Golian et al, 2018;Frolova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…are used for their structure stabilization (Kochubei- Lytvynenko et al, 2018a;Ondrušíková et al, 2019;Kumbár et al, 2017). Free moisture is suitable environment for biochemical transformations, that is why during production and storage of butter pastes there is a danger of biochemical transformations of milk fat and other components, primarily proteins and carbohydrates limiting storage life of such products (Golian et al, 2018;Frolova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is known from the literature that about 1% of iron reaches the roots of plants from the soil, and 0,25-0,3% enters the grass [30,31]. We found that the largest amount of iron was accumulated in the above-ground mass of A. ludoviciana (more than 300 µg), which can serve as a source of iron in the human body when consuming the plant with herbal tea.…”
Section: ô³ç³îëîã³ÿ ðîñëèímentioning
confidence: 63%
“…They are a source of biologically active substances and components that ensure the stability of quality indicators of final products during its storage.It was found that adding spices to the normalized mixture before thermal conditioning in the amount of 1.0 ± 0.2% leads to a decrease in the active acidity of goat milk and serum, allocated during processing of rennet in an average of 0.2 pH units. Besides, it provides the formation of a denser clot, accelerates serum separation, probably due to the adsorption of components of spices on the surface of casein micelles and, as a result, a decrease in their surface charge and aggregation [39].…”
Section: Analysis Of the Current State Of Technology Of Soft Cheesementioning
confidence: 99%